Seismic and Wind Analysis of Natural Draught Cooling Tower with Change in Dimensional Ratio - Hussain, Mohd Atif; Sakalle, Prof. Rashmi (International Journal of Scientific Research in Civil Engineering, 2021)
In this study, a static linear Eigen value buckling parametric analysis is done for cooling tower shell geometries of 150 m height. The shells are subjected to wind pressures (speeds) of (47 meter per second) and seismic vibrations under zone IV to observe the trends in the critical buckling pressures/speeds at which the shell first buckles and therefore the corresponding buckling modes. The cooling tower’s geometry is changed in a systematic manner along the height to obtain the relationship between applied wind speeds and seismic vibrations associated with the mode of buckling and the cooling tower’s geometry. Geometrical parameter ratios of the cooling tower’s dimensions are considered so as to hide a wider spectrum of the cooling tower’s geometry. The critical wind speed and seismic vibrations versus height curve is observed to be similar to the Euler buckling curve. There is an assumed diameter to total height ratio of about 1.15 instead of 1.5 for any cooling tower at which the critical wind speed is maximum. The critical wind speed varies linearly with the cooling system thickness and non-linearly with all diameter ratios. A linear eigen value vibration, parametric analysis is expressed for various cooling tower shell geometries to analyse trends in the free vibration response (natural frequencies and mode shapes). The forced response of the cooling tower to various forcing frequencies of wind and seismic vibrations is analysed using the mode analysis method using Staad.pro software. The shells are subjected to increasing wind gust periods of an equivalent speed to get the trends within the forced vibration response. In a systematic ladder manner, the cooling tower geometry is changed to obtain the free and forced vibration behaviour. The natural frequencies and their corresponding for the four different modes reduce with increasing height based on the loads applied. They are generally invariant with the peak to top diameter ratio, but the bandwidth increases with increasing height to top diameter ratio. The static response frequencies and their corresponding generally increase with increasing height as well as the height to base diameter ratios. The static response frequency generally decreases with decreasing forcing frequency.. The findings can be used as a basis for further research and establishment of conceptual design guidelines when considering stability, free and  forced vibration cooling tower_behaviour.
Keywords: Hyperbolic Cooling Tower; Stability; Buckling; Modes; Critical Wind Pressure; Speed/velocity; Seismic Vibrations; Static Response; Natural Frequency; Mode Shape